Analisis Hukum Islam ‎ terhadap Alasan-alasan Perceraian di ‎Indonesia - Makinuddin Makinuddin (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2010)
Among muslim community in indonesia, husbands often carelessly declare talaq to their wives without considering its consequence. Predictably, this custom is legalized by classical islamic jurisprudence stating that talaq is solely the right of husbands. This very stipulation is also supported by certain religious leaders. On the other hand, the regulation in Indonesia especially article 39 (2) of the interpretation to Law No. 1/1974; article 19 of Government Degree No. 5/1979; Law No. 7/1989 jo Law No. 3/2006 and article 116 of Compilation of Islamic Law all stipulate that talaq and divorce must only be permitted if there is legitimate reason for doing so and declared exclusively in front of court proceeding. It means that talaq by husbands and divorce by wifes is invalid if the reason is not justified or not heard by judges. In this point, classic muslim jurists disgree whether talaq can only be declared after fulfilment of certain conditions. Still, those believing that talaq should be based on certain reasons is more realistic considering that talaq is the most abhorred halal in islam and therefore should be discouraged.